KAJIAN KOMPARATIF ATAS FAKTOR-FAKTOR PEMBENTUK ORGANIZATION CITIZENSHIP BEHAVIOR (Kasus pada Institusi Pelayanan Publik versus Perusahaan Konvensional) - Siti Nurhayati; Wenti Ayu Sunarjo (Fakultas Ekonomi Universitas Pekalongan, 2019)
This study aims to examine the differences of the factors that can influence the Organization Citizenship Behavior (OCB) between those applied to conventional companies and those applied to public service organizations. The object of research under study is PT. Pismatex Pekalongan and regional public hospital Bendan Pekalongan City,where the unit of analysis is employers. The sample consisted of employees in both objects, amounting to 94 and 64 people. Processing data by descriptive method. The results indicate that the influence’s factor in OCB are applied in conventional companies is significant different in public service organizations. In more detail the results of hypothesis testing known that in conventional companies, the variables of job satisfaction, gender, and age of employees dominate the effect is OCB more than other variables. Whereas in public service organizations, the more dominant variables affecting OCB is organizational climate. Keywords: Organization Citizenship Behavior